Intrinsic Mitochondrial Nutrient Utilization May Underlie the Association of Metabolite Levels with BMIz and Insulin Resistance (FS03-02-19). (13th June 2019) - LaBarre, Jennifer; Peterson, Karen; Hao, Wei; Kachman, Maureen; Tang, Lu; Perng, Wei; Zhou, Ling; Song, Peter X K; Karnovsky, Alla; Cantoral, Alejandra; Tellez-Rojo, Martha; Burant, Charles
Abstract: Objectives: To identify metabolites associated with BMIz and insulin resistance (IR) among 108 girls and 98 boys aged 8–14 years. We sought evidence of whether altered mitochondrial nutrient utilization, as indicated by mitochondrial-derived metabolites, mediates the relationship between diet, IR and obesity. Methods: Anthropometry, fasting untargeted-liquid chromatography/mass spectrometry-derived metabolites and C-Peptide, and semi-quantitative food frequency questionnaires were collected from adolescents in the Early Life Exposure in Mexico to ENvironmental Toxicants (ELEMENT) birth cohort. Sex-stratified generalized linear models were used to identify metabolites that are marginally associated BMIz and HOMA C-peptide (HOMA-CP), accounting for puberty, age and muscle and fat area (FDR < 0.1). Assessed the relationship between energy-adjusted macronutrient intake with HOMA-CP and BMIz. Structural equation models coupled with hierarchical clustering identified clusters of metabolites that may mediate the relationship between macronutrient intake with BMIz and HOMA-CP. Results: Stratification by sex demonstrated sex-specific associations with BMIz. Most notable were girl's positive association with diacylglycerols and boy's positive association with branched chain and aromatic amino acids, independent of HOMA-CP. Intermediates in fatty acid metabolism, including medium chain acylcarnitines (acylCN), were inversely associated with HOMA-CP. No direct relationship was observed between macronutrient intake with BMIz and IR. Using mediation analyses, fat intake is positively associated with BMIz and HOMA-CP through increases in levels of dicarboxylic fatty acids (DiC-FA), products of omega-oxidation. Carbohydrate intake is positively associated with HOMA-CP through decreases in levels of medium chain acylCN, products of β-oxidation. Conclusions: Insulin resistance in children appears to be associated with reduced fatty acid oxidation capacity. When consuming more grams of fat, there is evidence for increased extra-mitochondrial fatty acid metabolism (DiC-FA), while higher carbohydrate intake appears to lead to accumulation of intermediates of β-oxidation. Thus, biomarkers of IR and mitochondrial oxidative capacity may depend on macronutrient intake. Funding Sources: This work was supported by the NIEHS, EPA and NIDDK.